2016
DOI: 10.1089/cyber.2015.0208
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality–Enhanced Cognitive–Behavioral Therapy for Morbid Obesity: A Randomized Controlled Study with 1 Year Follow-Up

Abstract: It is well known that obesity has a multifactorial etiology, including biological, environmental, and psychological causes. For this reason, obesity treatment requires a more integrated approach than the standard behavioral treatment based on dietary and physical activity only. To test the long-term efficacy of an enhanced cognitive-behavioral therapy (CBT) of obesity, including a virtual reality (VR) module aimed at both unlocking the negative memory of the body and to modify its behavioral and emotional corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
117
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 47 publications
(45 reference statements)
3
117
0
11
Order By: Relevance
“…In eating disorders, virtual cue exposure to target urge to binge and anxiety associated with binge cues has been successfully used in the treatment of patients with binge eating (bulimia nervosa or binge eating disorders) who did not respond to standard CBT (Ferrer‐García et al, ). Furthermore, the use of virtual reality to “update” negative body representations stored in memory has been shown to improve the efficacy of CBT at one year in obese patients with binge eating disorder (Cesa et al, ; Manzoni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In eating disorders, virtual cue exposure to target urge to binge and anxiety associated with binge cues has been successfully used in the treatment of patients with binge eating (bulimia nervosa or binge eating disorders) who did not respond to standard CBT (Ferrer‐García et al, ). Furthermore, the use of virtual reality to “update” negative body representations stored in memory has been shown to improve the efficacy of CBT at one year in obese patients with binge eating disorder (Cesa et al, ; Manzoni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible modalities for this reduction in pain may be due to a reduction in pain‐related brain activity in the insula and thalamus, ie, how the brain processes pain and produces analgesia . Technology involving the use of visual biofeedback has been shown to improve quality of life, pain level, and physical function in patients with RA and SLE . Additionally, all participants reported that they would participate in a similar study again if given the opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…VR represents an important advance in biofeedback technologies by providing immersive and realistic multisensory experiences that can help alleviate symptomology by allowing patients to learn stress reduction and pain management skills . Previously, VR has been studied in a range of disease states, including obesity , anxiety disorders , acute pain management , oncology , and neurorehabilitation . Concurrent improvements in software and hardware design, as well as associated cost reductions, have made VR promising for more widespread accessibility in health care .…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive Behavioral Therapy involving VR exposure is effective for treating more severe psychological disorders such as Post-Traumatic Stress Disorder (Rothbaum et al, 2001; Difede and Hoffman, 2002; Freedman et al, 2010; Rizzo et al, 2010; Difede et al, 2014). VR has also been used to treat eating disorders (Manzoni et al, 2016; Wiederhold et al, 2016) and may help treat delusions (Freeman et al, 2016), self-criticism (Falconer et al, 2014); and patients with chronic pain (Botella et al, 2013; Garcia-Palacios et al, 2015). To our knowledge; no studies have tested VR as an intervention to facilitate mindfulness skills training for DBT®, nor are there any studies using VR to treat BPD, an unusually severe mental disorder.…”
Section: Introductionmentioning
confidence: 99%